2010
DOI: 10.3858/emm.2010.42.6.046
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of whole mitochondrial DNA in patients with MELAS and MERRF diseases

Abstract: Mitochondrial diseases are clinically and genetically heterogeneous disorders, which make the exact diagnosis and classification difficult. The purpose of this study was to identify pathogenic mtDNA mutations in 61 Korean unrelated families (or isolated patients) with MELAS or MERRF. In particular, the mtDNA sequences were completely determined for 49 patients. From the mutational analysis of mtDNA obtained from blood, 5 confirmed pathogenic mutations were identified in 17 families, and 4 unreported pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Mutation of the mitochondrial genome in genes encoding proteins for subunits of mitochondrial respiratory chain complexes IV, ribosomal RNA and transfer RNA have been associated with neurodegenerative diseases and cancer 1113. Inherited mitochondrial disease is considered a distinct entity predisposing individuals to heritable conditions such as chronic progressive external ophthalmoplegia, lebers hereditary optic neuropathy and mitochondrial myopathy, encephalopathy, lactic acidosis and stroke syndrome 14. Furthermore, type-1 tumour necrosis factor receptor (TNFR1) mutant cells show evidence of altered mitochondrial function paralleled by increased oxidative capacity and mitochondrial ROS generation, blockade of which resulted in reduced proinflammatory cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of the mitochondrial genome in genes encoding proteins for subunits of mitochondrial respiratory chain complexes IV, ribosomal RNA and transfer RNA have been associated with neurodegenerative diseases and cancer 1113. Inherited mitochondrial disease is considered a distinct entity predisposing individuals to heritable conditions such as chronic progressive external ophthalmoplegia, lebers hereditary optic neuropathy and mitochondrial myopathy, encephalopathy, lactic acidosis and stroke syndrome 14. Furthermore, type-1 tumour necrosis factor receptor (TNFR1) mutant cells show evidence of altered mitochondrial function paralleled by increased oxidative capacity and mitochondrial ROS generation, blockade of which resulted in reduced proinflammatory cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The clinical hallmark of MELAS is stroke-like episodes that cause the abrupt onset of focal neurological deficits at a young age. Neuroimaging studies and measurement of blood lactate are useful screening tests for the diagnosis of MELAS, though the definite diagnosis of MELAS relies on the ragged red fibers (RRFs) or strongly succinate dehydrogenase-stained vessels (SSVs) demonstrated by muscle biopsy, or the causative mtDNA mutation confirmed by molecular genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although the A3243G mutation is the most prevalent MELAS mutation, recent studies showed the mtDNA A3243G point mutation only appeared in 23% of Korean MELAS patients. 9 Furthermore, the T3271C mutation was rarely reported in other countries than Japan. 7,15 These data suggest that the mutation pattern of MELAS can be different in different geographically localized populations.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in other studies (Bai and Wong, 2004;Genasetti et al, 2007;Sakiyama et al, 2011), using ARMS, we were able to detect variable proportions of the m.1624C>T mutation. The proportion of heteroplasmic mtDNA is generally one determinant of phenotypic severity (Choi et al, 2010;Laloi-Michelin et al, 2009). Compared with the severely affected Leigh syndrome-like siblings with homoplasmic m.1624C>T mutation, our heteroplasmic cases showed milder phenotypes with respect to the age of onset and clinical features (Table 5); the lower proportion of mutant mtDNA might be responsible for this.…”
Section: Discussionmentioning
confidence: 77%